Photoelectrochemical properties of the CT1 dye: A DFT study - Camino, B.; De La Pierre, Marco; Ferrari, A. (Elsevier, 2013)
We report a comprehensive computational study on the electronic and optical properties of a hemi-squaraine organic dye recently proposed for Dye Sensitized Solar Cells (DSSCs) applications. Ground and excited state properties have been computed within DFT and TD-DFT approaches, respectively. Results from 10 different functionals ranging from pure GGA (mPW91 and PBE), to global hybrids (B3LYP, PBE0, mPW1K and M05-2X) and range separated hybrids (ω-B97X, LC-ωPBE, CAM-B3LYP and HSE06) have been analyzed and compared to available experimental data. Aggregation effects on the electrochemical and optical properties of the dye have been also analyzed.